Pelatihan Manajemen Keuangan Pada Pelaku UMKM di Desa Bubun Kecamatan Tanjung Pura Kabupaten Langkat - Muhammad Arfan Harahap; Ahmad Daud; Asmawarna Sinaga (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
This community service activity is one of the implementation of the tri dharma of higher education carried out by the Jam'iyah Mahmudiyah Islamic High School Tanjung Pura Langkat. The purpose of this community service activity is to provide knowledge and understanding to MSME actors in managing their finances. Financial management assists MSME actors in ensuring the sustainability of their business. The main problem faced by MSME actors in managing their finances is the lack of knowledge and the tendency for traditional financial management to be done. Therefore, financial management training activities are needed to answer the problems faced by MSME actors. The community service method used in this activity is the participation method. Financial management training was applied to MSME actors in Langkat Regency, especially in Bubun Village, Tanjung Pura District. The result of this community service activity is that the training participants gain knowledge and understand how important financial management is and how to manage finances professionally. Keywords: Financial Management, MSMEs, Training